Magnetic Resonance Spectroscopy. (September 2017) - Rhodes, Christopher J.
Since the original observation by Zeeman, that spectral lines can be affected by magnetic fields, 'magnetic spectroscopy' has evolved into the broad arsenal of techniques known as 'magnetic resonance'. This review focuses on nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), and muon spin resonance (μSR): methods which have provided unparalleled insight into the structures, reactivity and dynamics of molecules, and thereby contributed to a detailed understanding of important aspects of chemistry, and the materials, biomedical, and environmental sciences. Magnetic resonance imaging (MRI), in vivo magnetic resonance spectroscopy (MRS) and functional magnetic resonance spectroscopy (fMRS) are also described. EPR is outlined as a principal method for investigating free radicals, along with biomedical applications, and mention is given to the more recent innovation of pulsed EPR techniques. In the final section of the article, the various methods known as μSR are collected under the heading 'muon spin resonance', in order to emphasise their complementarity with the more familiar NMR and EPR.